Myelolipoma of the Pelvis: A Case Report and Review of Literature - Sethi, Seema; Thakur, Shivam; Jacques, Suzanne; Aoun, H. D.; Tranchida, Paul (Frontiers in Oncology, 2018)
Myelolipomas are uncommon, benign tumors which typically occur in the adrenal glands and consist of mature adipose tissue and benign hematopoietic components. Myelolipomas can occur outside of the adrenal glands, but the presacral region, retroperitoneum, pelvis, and mediastinum are unusual locations for these tumors. It is important to recognize this entity in these locations since they can attain massive sizes leading to pressure symptoms and need to be differentiated from the malignant tumors like liposarcomas. We present a myelolipoma case in the presacral region. Our case illustrates the clinical approach of these tumors in such unusual locations.